PENERAPAN TEORI-TEORI FILOSOFIS DALAM MENAFSIRKAN AL-QUR’AN - Ikhlas Budiman (Tanzil: Jurnal Studi Al-Quran, 2015)
Human reason is a tool to understand the realities and to express them in the philosophical theories. Since the Koran suggests human to use their reason, then the philosophical theories as the results of the use of reason can be used to understand and interpret verses of the Koran. This paper describes the application of that philosophical theories to the Quranic verses as a mode of interpretation of the Koran, such as: the theory of the fundamental reality and unity of existence, the theory of gradation, the theory of existence-in-itself and existence-in-something-else, the theory of quiddity, the theory of cause and effect, the theory of every faculty happiness in achieving its essence demands without obstacles, the theory of the substantial motion, and the theory of the lowest thing having the potentiality to become the higher.